(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Organ transplantation is a critical treatment for end-stage organ failure, but the preservation of donor organs remains a significant challenge that impacts transplantation success. This study explores novel organ preservation techniques, including normothermic machine perfusion (NMP), hypothermic machine perfusion (HMP), and ex vivo organ culture, to assess their effects on organ viability and transplantation outcomes. Using a multicenter, experimental approach, we evaluated kidney, liver, and heart transplants from brain-dead donors, comparing traditional cold storage with advanced preservation methods. The results demonstrated that NMP and HMP provided superior outcomes in organ viability, reducing ischemic injury and enhancing post-transplant function. However, variability in organ response and the lack of standardized protocols remain critical challenges. The findings suggest that further research is needed to refine preservation strategies, optimize individualized approaches based on donor factors, and investigate the long-term impact on graft survival and rejection. The integration of emerging technologies, such as artificial intelligence and nanotechnology, holds promise in revolutionizing organ preservation methods.